2020
DOI: 10.1177/2055207620968355
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence and the future of psychiatry: Qualitative findings from a global physician survey

Abstract: Background The potential for machine learning to disrupt the medical profession is the subject of ongoing debate within biomedical informatics. Objective This study aimed to explore psychiatrists’ opinions about the potential impact innovations in artificial intelligence and machine learning on psychiatric practice Methods In Spring 2019, we conducted a web-based survey of 791 psychiatrists from 22 countries worldwide. The survey measured opinions about the likelihood future technology would fully replace phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(95 citation statements)
references
References 72 publications
1
72
0
1
Order By: Relevance
“…31 Jha et al 31 developed a survey instrument to measure American physicians' perceptions about the impact of health information systems on primary care delivery, and found that physicians were sceptical about its ability to perform better than humans. A qualitative study measuring psychiatrists perceptions of AI role replacement, 32 found that their views were divergent about the value and impact of AI, but that it would never replace the relational aspects of psychiatric care. Laı¨et al 33 used a qualitative approach to study physicians' perceptions of AI, and found that they share concerns about the management of data, the development of knowledge, the upheaval of the doctor-patient relationship, and the disruption of the diagnosis and decision-making landscape.…”
Section: Workforce Perception Of Aimentioning
confidence: 99%
“…31 Jha et al 31 developed a survey instrument to measure American physicians' perceptions about the impact of health information systems on primary care delivery, and found that physicians were sceptical about its ability to perform better than humans. A qualitative study measuring psychiatrists perceptions of AI role replacement, 32 found that their views were divergent about the value and impact of AI, but that it would never replace the relational aspects of psychiatric care. Laı¨et al 33 used a qualitative approach to study physicians' perceptions of AI, and found that they share concerns about the management of data, the development of knowledge, the upheaval of the doctor-patient relationship, and the disruption of the diagnosis and decision-making landscape.…”
Section: Workforce Perception Of Aimentioning
confidence: 99%
“…In qualitative research a common prediction among physicians is that, by liberating health professionals from administrative tasks, AI/ML will indirectly facilitate more time with patients thereby enhancing levels of empathy. (11,15) Survey research also indicates skepticism among physicians that AI/ML will be able to directly substitute for, or augment clinicians, in the provision of empathic care. (1012,15)…”
Section: Discussionmentioning
confidence: 99%
“…(11,15) Survey research also indicates skepticism among physicians that AI/ML will be able to directly substitute for, or augment clinicians, in the provision of empathic care. (1012,15)…”
Section: Discussionmentioning
confidence: 99%
“…Considering these digital advances, educating future clinicians, including psychologists and psychotherapists, will be important to ensure optimal, safe use of AI/ML enabled tools and innovations. So far, a growing number of investigations have explored the views of clinicians including primary care physicians on the impact of AI/ML tools on their job (3)(4)(5)(6)(7). These studies, albeit limited, suggest that mental health clinicians expect AI/ML to influence or change their professional roles in the future.…”
Section: Introduction Backgroundmentioning
confidence: 99%